Reflection-in-Action Teaching Strategies Used by Faculty to Enhance Teaching and Learning - Dr. Cindy Giaimo-Ballard; Dr. L. Hyatt (Networks: An Online Journal for Teacher Research, 2012)
Scholars have suggested that reflective strategies are vital to teaching and learning (Brookfield, 1998; Dewey, 1964; Rogers, 2001; Schön, 1983, 1987; Zeichner, 1996). Additionally, accrediting institutions recognize the importance of reflective practice and include the requirement in their standards. However, little direction is given to faculty regarding reflective methods and processes, and it is unclear how faculty members apply the process of reflection. To elucidate these processes, this study explored the phenomenon of reflection-in-action regarding teaching from the perspectives of faculty from institutions accredited by the National Council for Accreditation of Teacher Education (NCATE), using Schön’s (1983, 1987) concept of reflection-in-action as the conceptual framework and interviewing as the primary method of data collection. Analysis of the data allowed for determination that the participants practiced the reflective teaching strategies of (a) note taking, (b) requesting feedback, (c) setting up checkpoints, and (d) adjusting to improve practices while performing observation in practice. Participants also noted that partaking in the NCATE accreditation process encouraged reflective strategies for the improvement of teaching and learning.